Discovery of 2-Pyridylpyrimidines as the First Orally Bioavailable GPR39 Agonists - Peukert, Stefan (American Chemical Society, 2014)
[Image: see text] The identification of highly potent and orally bioavailable GPR39 agonists is reported. Compound 1, found in a phenotypic screening campaign, was transformed into compound 2 with good activity on both the rat and human GPR39 receptor. This compound was further optimized to improve ligand efficiency and pharmacokinetic properties to yield GPR39 agonists for the potential oral treatment of type 2 diabetes. Thus, compound 3 is the first potent GPR39 agonist (EC(50)s ≤ 1 nM for human and rat receptor) that is orally bioavailable in mice and robustly induced acute GLP-1 levels.